The use of virtual reality in environment experiences and the importance of realism. (February 2022) - Newman, M.; Gatersleben, B.; Wyles, K.J.; Ratcliffe, E.
Abstract: Introduction: Virtual reality (VR) can be extremely useful in simulating nature when physical presence is not possible. Additionally, it allows for environments to be customised (e.g., weather, or topography) and facilitates the design of controlled experimental settings. However, VR can involve the use of expensive equipment and complex software to create highly realistic immersive experiences. But is it necessary for experiences to rival the latest Hollywood blockbuster? This paper explores whether such investment can be valuable in research on nature experiences. Studies: Two studies were conducted to examine how realism of environmental presentations impact affective responses and participant perceptions. Study One ( n = 16) explored perceptions of the same lake presented to participants in the real world, in VR and as a video. Study Two ( n = 120) compared participant's affective responses to one of four possible virtual environments differing in level of realism ( high or low ) and type ( natural or built ). Results: Study One showed that experiences of VR presentations fell between real and video presentations. Study Two found that more realistic VR environments evoked more positive affective and serenity responses, as well as a greater sense of presence. In both studies, participants stressed the importance of naturalistic interaction, sensory immersion, and graphical realism in the experiences, which may help explain these effects. Conclusion: The level of realism that can be attained with VR does impact affective responses and perceptions. Investment in VR for future research can be highly beneficial. Highlights: Virtual reality (VR) enables highly realistic immersive experiences. Two VR studies examined how level of realism impacted affective responses. VR can elicit similar positive affective responses to a real natural scene. High realism VR environments provided a greater sense of presence and restoration. Realism is important, particularly for environmental restoration research.